Reconstruction of Plastid Proteomes of Apicomplexans and Close Relatives Reveals the Major Evolutionary Outcomes of Cryptic Plastids. (5th January 2023) - Mathur, Varsha; Salomaki, Eric D; Wakeman, Kevin C; Na, Ina; Kwong, Waldan K; Kolisko, Martin; Keeling, Patrick J
Abstract: Apicomplexans and related lineages comprise many obligate symbionts of animals; some of which cause notorious diseases such as malaria. They evolved from photosynthetic ancestors and transitioned into a symbiotic lifestyle several times, giving rise to species with diverse non-photosynthetic plastids. Here, we sought to reconstruct the evolution of the cryptic plastids in the apicomplexans, chrompodellids, and squirmids (ACS clade) by generating five new single-cell transcriptomes from understudied gregarine lineages, constructing a robust phylogenomic tree incorporating all ACS clade sequencing datasets available, and using these to examine in detail, the evolutionary distribution of all 162 proteins recently shown to be in the apicoplast by spatial proteomics in Toxoplasma. This expanded homology-based reconstruction of plastid proteins found in the ACS clade confirms earlier work showing convergence in the overall metabolic pathways retained once photosynthesis is lost, but also reveals differences in the degrees of plastid reduction in specific lineages. We show that the loss of the plastid genome is common and unexpectedly find many lineage- and species-specific plastid proteins, suggesting the presence of evolutionary innovations and neofunctionalizations that may confer new functional and metabolic capabilities that are yet to be discovered in these enigmatic organelles.